Analisis User Experience pada Pengguna Aplikasi Dompet Digital Menggunakan Teori Jacob Nielsen - Achyani, Yuni Eka; Kezia Widyana (STMIK Palangkaraya, 2024)
Digital wallets are one of the fastest-growing types of fintech. Digital wallets are just like real wallets. Users can make transactions either online or offline to be more effective and efficient. It is important for the development team to pay attention to the comfort and satisfaction of its users. The purpose of writing, to find out the rate obtained by each application and will be tested using the usability testing method. This is done to evaluate the usability of digital wallet applications based on the responses given by users after interacting with the product system. The research was conducted in the DKI Jakarta area using 3 digital wallets and involving 150 digital wallet respondents, including: 51 Shopee pay Respondents, 52 Go-pay Respondents and 47 DANA Respondents. The results of the tests that have been carried out, it can be concluded that the Shopee-pay Digital Wallet is in the Very Good category with a score of 4.35, the Go-pay and DANA applications are in the good category with the Go-Pay application score of 3.98 and DANA 4.16. This shows that the three applications have fulfilled the five aspects of usability testing: learnability, memorability, efficiency, errors and satisfaction.